1982
DOI: 10.1002/aja.1001650403
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear size as a cell‐kinetic marker for osteoblast differentiation

Abstract: A nuclear morphometric assay for preosteoblasts is introduced as a cell-kinetic technique, applicable to routine histological preparations of mineralized tissue. Because this method is a morphological marker for osteoblast precursor cell differentiation, it provides a new dimension for determining the mechanism of osteoblast histogenesis. Osteoblast precursors of the periodontal ligament are a mixed population of progenitors, kinetically separable into two distinct groups according to nuclear size. Preosteobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 27 publications
6
96
0
Order By: Relevance
“…The cuboidal cells showing a highly intense positive signal for Osn and Osc "As in a punctate perinuclear arrangement at the distal surface of the interradicular septum lined up on the active bone-formation surface and gathered into several layers at the distal surface of the crest of the interradicular septum. It is reported that osteogenic precursor cells have large, pale-staining nuclei compared with non-osteogenic cells, which have small nuclei with dense chromatin (33). Therefore, these cuboidal cells were designated as osteoblasts and osteoprogenitor cells in a zone close to the alveolar bone surface within the PDL space.…”
Section: Osteogenic Cells In the Periodontal Ligament Express Osn Andmentioning
confidence: 99%
“…The cuboidal cells showing a highly intense positive signal for Osn and Osc "As in a punctate perinuclear arrangement at the distal surface of the interradicular septum lined up on the active bone-formation surface and gathered into several layers at the distal surface of the crest of the interradicular septum. It is reported that osteogenic precursor cells have large, pale-staining nuclei compared with non-osteogenic cells, which have small nuclei with dense chromatin (33). Therefore, these cuboidal cells were designated as osteoblasts and osteoprogenitor cells in a zone close to the alveolar bone surface within the PDL space.…”
Section: Osteogenic Cells In the Periodontal Ligament Express Osn Andmentioning
confidence: 99%
“…Fibroblastic cells of the PDL have also been suggested to be a source of osteoblasts for continued remodeling of alveolar bone of the mandibula (Roberts et al, 1982). Therefore, PDL fibroblastic cells have been suggested to be multipotent cells (McCulloch and Bordin, 1991) or composed of heterogenous cell populations that have the capacity to differentiate into either osteoblasts or cementoblasts depending on the microenvironment (Gould et al, 1980;Roberts et al, 1982;McCulloch and Melcher, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…(a) Recruitment and proliferation of osteoblasts Investigators have used the rat model to determine proliferation rates of periodontal cells by measuring the rate of DNA synthesis (Smith and Roberts, 1980;Roberts and Chase, 1981), to define a differentiation pathway of osteoblast precursors using nuclear size markers (Roberts et al, 1982), and to measure the rate of collagenous matrix synthesis by metabolic labeling with radioisotopes in intact animals (Koumas and Matthews, 1969;Diaz, 1978) and in cultured alveolar bone explants (Duncan et al, 1984). There were earlier attempts to use the mouse tooth movement model to exploit the advantages of a smaller animal, such as the presentation of larger areas of paradental tissues and teeth on the same microscopic slide.…”
Section: (I) Introductionmentioning
confidence: 99%
“…The pathway of osteoblast differentiation in physiological condition and after mechanical stimulation of the periodontium was investigated by means of a gradient of nuclear sizes as markers for the levels of osteoblast maturation (Roberts et al, 1982;Roberts and Morey, 1985). In another histomorphometric study, which reported a correlation between an increase in bone formation rate and an increase in the numbers of active osteoblasts (King et al, 1991b), the authors recognized that the onset of bone formation is achieved by both the proliferation and increased function of each individual osteoblast.…”
Section: (I) Introductionmentioning
confidence: 99%